"Yo-ho, A Pirates Life For Me" – Queer Positionalities, Heteronormativity, and Piracy in Pirates of the Caribbean. A Queer Reading. - Steinhoff, Heike (Current Objectives of Postgraduate American Studies, 2012)
At first sight Walt Disney's box office hit Pirates of the Caribbean: The Curse of the Black Pearl“ (2003) appears as a product of Hollywood's (hetero)normative blockbuster industry. It is a film that apparently caters for the needs of contemporary western mainstream audiences. Yet, as this paper will argue, the movie is fused with potentially queer elements, moments, and signifiers. Drawing on a broad working definition of 'queer,' this paper will present a 'queer reading' of the film. It will elucidate how Pirates of the Caribbean“ lends itself to such a reading not only due to the ambivalent and campy figure of Captain Jack Sparrow, but also due to the film's only seemingly classical narrative structure and protagonists. Moreover, it will analyze the figure of the pirate in the light of Foucauldian heterotopias.